AI Planning in Web Services Composition: a review of current approaches and a new solution - Digiampietri, Luciano A.; Pérez-Alcázar, José J.; Medeiros, Claudia Bauzer (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2007: Anais do VI Encontro Nacional de Inteligência Artificial, 2007)
Web services represent a relevant technology for interoperability. An important step toward the development of applications based on Web services is the ability of selecting and integrating heterogeneous services from different sites. When there is no single service capable of performing a given task, there must be some way to adequately compose basic services to execute this task. The manual composition of Web services is complex and susceptible to errors because of the dynamic behavior and flexibility of the Web. This paper describes and compares AI planning solutions to Web service automatic composition. As a result of this comparison, it proposes an architecture that supports service composition, and which combines AI planning with workflow mechanisms.